Combustion characteristics of pure rapeseed oil fuel after injection in a constant volume combustion chamber with a non-road mobile machinery engine solenoid injector. (15th July 2022) - Emberger, Peter; Altmann, Robert; Gebhard, Jürgen; Thuneke, Klaus; Winkler, Markus; Töpfer, Georg; Rabl, Hans-Peter; Remmele, Edgar
Highlights: Injection and combustion with a high-pressure solenoid injector are researched. Hydraulic behaviour of rapeseed oil is differing from diesel fuel. Injection pressure has a higher impact on rapeseed oil combustion compared to diesel. Rapeseed oil shows delayed ignition at low load and advanced ignition at high load. With adjusted injection settings a similar heat release is possible for both fuels. Abstract: Pure rapeseed oil fuel (R100) according to standard DIN 51605 is a greenhouse gas saving option for the mobility sector. With its high energy density close to diesel fuel, R100 is suitable to operate non-road mobile machinery with a high power demand and long operating time, where electric drives reach their limits. Advantages are indicated for its use in environmentally sensitive areas like agriculture since R100 is highly biodegradable and non-toxic. However, R100 is characterised by differing physical and chemical properties compared to diesel. The objective of the research is to investigate the differences in the ignition and combustion behaviour of R100 compared to diesel fuel (DF). For this purpose, a constant volume combustion chamber is used, which is equipped with a modern solenoid injector for engines of non-road mobile machinery. The researched injector shows a different hydraulic behaviour when using R100 compared to DF in that the injected fuel mass is lower with R100 than with DF. In combination with the 14 % by mass lower calorific value, less energy output is determined with R100. When varying the injection pressure, the impact on the ignition delay and combustion behaviour is much higher for R100 than for DF. Specifically, an increase of the injection pressure supports mixture preparation and thus partially compensates the differing physical properties of R100. The results of ignition delay measurements and net heat release analysis are as follows: At low load conditions with low injection pressure as well as a low combustion chamber temperature and pressure, R100 ignites later and shows a further delayed combustion compared to diesel. The opposite is observed for medium and high load conditions, where R100 ignites faster and without delayed combustion in comparison to DF. Thus, an adjustment of the heat release of R100 at the same level as for DF is possible by modifying the injection strategy. The research shows that for an optimised combustion of R100 the injection settings must be adjusted for every operation point separately. The results indicate how the injection parameters should be adjusted for different load conditions to realise a high-quality engine calibration for R100.